Ask me why: Patterns of intrahousehold decision-making - Bernard, Tanguy; Doss, Cheryl R.; Hidrobo, Melissa; Hoel, Jessica B.; Kieran, Caitlin (Elsevier, 2020)
Households are sites of both cooperation and contestation. With more data available at the intrahousehold level, development researchers and practitioners have increasingly focused on household dynamics and decision-making and how these relate to outcomes of interest across many domains such as health and agriculture. Many researchers who wish to better understand power dynamics within households have focused on the question of who makes decisions in the household. A woman’s participation in household decision-making is often used both as a proxy for empowerment, an end in its own right, and as a means to achieve better production and consumption outcomes. However, research on this topic pays less attention to why different household members may make different decisions, and whether this matters for individual or household welfare. In this paper, we use an innovative methodology to look beyond the identity of the decision-maker to explore the reasons that may drive patterns of household decision-making. We then assess whether the rationale behind who makes household decisions helps explain variation in household outcomes, above and beyond what is explained by the identity of the decision-maker. Our approach uses vignettes, which are survey instruments used to measure concepts that are more easily defined by examples.1 Vignettes have been used to measure subjective well-being (Ravallion, Himelein, & Beegle, 2016), women’s agency (see Donald, Koolwal, Annan, Falb, & Goldstein, 2017 for a review), bias against women politicians (Beaman, Chattopadhyay, Duflo, Pande, & Topalova, 2009), as well as risk aversion (Barter & Renold, 1999). However, this is the first time that they have been used to analyze the processes of household decision-making.